Towards harmonizing clinical linear energy transfer (LET) reporting in proton radiotherapy: a European multi-centric study. (1st February 2022) - Hahn, Christian; Ödén, Jakob; Dasu, Alexandru; Vestergaard, Anne; Fuglsang Jensen, Maria; Sokol, Olga; Pardi, Claudia; Bourhaleb, Faiza; Leite, Amélia; de Marzi, Ludovic; Smith, Edward; Aitkenhead, Adam; et al.
Abstract: Background: Clinical data suggest that the relative biological effectiveness (RBE) in proton therapy (PT) varies with linear energy transfer (LET). However, LET calculations are neither standardized nor available in clinical routine. Here, the status of LET calculations among European PT institutions and their comparability are assessed. Materials and methods: Eight European PT institutions used suitable treatment planning systems with their center-specific beam model to create treatment plans in a water phantom covering different field arrangements and fulfilling commonly agreed dose objectives. They employed their locally established LET simulation environments and procedures to determine the corresponding LET distributions. Dose distributions D 1.1 and DRBE assuming constant and variable RBE, respectively, and LET were compared among the institutions. Inter-center variability was assessed based on dose- and LET-volume-histogram parameters. Results: Treatment plans from six institutions fulfilled all clinical goals and were eligible for common analysis. D 1.1 distributions in the target volume were comparable among PT institutions. However, corresponding LET values varied substantially between institutions for all field arrangements, primarily due to differences in LET averaging technique and considered secondary particle spectra. Consequently, DRBE using non-harmonized LET calculations increased inter-center dose variations substantially compared to D 1.1 and significantly in mean dose to the target volume of perpendicular and opposing field arrangements ( p < 0.05). Harmonizing LET reporting (dose-averaging, all protons, LET to water or to unit density tissue) reduced the inter-center variability in LET to the order of 10–15% within and outside the target volume for all beam arrangements. Consequentially, inter-institutional variability in DRBE decreased to that observed for D 1.1 . Conclusion: Harmonizing the reported LET among PT centers is feasible and allows for consistent multi-centric analysis and reporting of tumor control and toxicity in view of a variable RBE. It may serve as basis for harmonized variable RBE dose prescription in PT.